2017
DOI: 10.1111/1348-0421.12533
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HLA‐DRA and CD74 mRNA in whole blood during the course of complicated and uncomplicated Staphylococcus aureus bacteremia

Abstract: To improve management of Staphylococcus aureus bacteremia (SAB), better understanding of host-pathogen interactions is needed. In vitro studies have shown that S. aureus bacteria induce dose-dependent immunosuppression that is evidenced by reduced expression of major histocompatibility complex (MHC) class II on antigen presenting cells. Thus, the aim of this study was to determine whether expression of the MHC class II-related genes HLA-DRA and CD74 is more greatly reduced in complicated SAB, with its probable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…A suppressed immune response involving downregulated mRNA expression of NLRP1 accompanied by normal levels of IL1B and CASP1 mRNAs has been observed in ex vivo stimulated monocytes in patients with trauma, and reduced NLRP3 gene expression in patients suffering polytrauma has also been discussed . In addition, the patients with complicated SAB in the present study displayed downregulated mRNA levels of the immunosuppression marker human leucocyte antigen‐DRA, HLA‐DRA , recently shown by our group, indicating an immunocompromised state …”
Section: Discussionsupporting
confidence: 82%
“…A suppressed immune response involving downregulated mRNA expression of NLRP1 accompanied by normal levels of IL1B and CASP1 mRNAs has been observed in ex vivo stimulated monocytes in patients with trauma, and reduced NLRP3 gene expression in patients suffering polytrauma has also been discussed . In addition, the patients with complicated SAB in the present study displayed downregulated mRNA levels of the immunosuppression marker human leucocyte antigen‐DRA, HLA‐DRA , recently shown by our group, indicating an immunocompromised state …”
Section: Discussionsupporting
confidence: 82%
“…In vitro studies have shown that S aureus can reduce the expression of major histocompatibility complex (MHC) class II on antigen presenting cells 59 . The expression of the MHC class II‐related genes HLA‐DRA and CD74 is significantly reduced in complicated S aureus bacteremia (SAB) than in uncomplicated SAB, indicating that there is an association between complicated SAB and reduced MHC class II expression 60 . It is not clear yet why the HLA‐DP expression upregulated in thymus after S aureus infection.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that decreased CD74 mRNA expression significantly predicted 28-day mortality following septic shock. Expression of the MHC class II-related genes HLA-DRA and CD74 was investigated in patients with complicated and uncomplicated Staphylococcus aureus bacteremia (SAB) [219]. The complicated SAB group included patients with hematogenous seeding or extension of infection beyond the primary focus, etc.…”
Section: Human Leukocyte Antigen D-related-hla-dr Expression On Monoc...mentioning
confidence: 99%